Response of triploid Atlantic salmon (Salmo salar) to commercial vaccines. Issue 97 (February 2020) - Chalmers, Lynn; Migaud, Herve; Adams, Alexandra; Vera, Luisa M.; McStay, Elsbeth; North, Ben; Mitchell, Chris; Taylor, John F.
Abstract: While triploid Atlantic salmon represent a practical and affordable solution to the issues associated with sexual maturation in the salmonid aquaculture industry, empirical evidence suggests triploids are more susceptible to disease and vaccine side-effects than diploids. With vaccination now part of routine husbandry, it is essential their response be studied to confirm their suitability for commercial production. This study tested the response of triploid and diploid Atlantic salmon to vaccination with commercially available vaccines. Triploid and diploid Atlantic salmon siblings were injected with one of three commercial vaccines (or sham-vaccinated) and monitored for performance throughout a commercial production cycle. Sampling at smolt and harvest was undertaken along with individual weight and length assessments through the cycle. Antibody response to Aeromonas salmonicida vaccination was similar in both ploidy, with a positive response in vaccine-injected fish. For both adhesions and melanin, analysis found that higher scores were more likely to occur as the anticipated severity of the vaccine increased. In addition, for adhesion scores at smolt and melanin scores at smolt and harvest, triploids were statistically more likely to exhibit high scores than diploids. Triploids maintained a significantly higher body weight during freshwater and until 11 months post-seawater transfer, with diploids weighing significantly more at harvest. Growth, represented by thermal growth coefficient (TGC), decreased in both ploidy as the severity of adhesions increased, and regression patterns did not differ significantly between ploidy. Vertebral deformity prevalence was consistently higher in triploids (smolt 12.3 ± 4.5%; harvest 34.9 ± 5.9%) than diploids (smolt 0.8 ± 0.5%; harvest 15.9 ± 1.9%), with no significant difference between vaccine groups in each ploidy. This study demonstrates that triploids respond as well to vaccination as diploids and provides further supporting evidence of triploid robustness for commercial aquaculture. Highlights: Antibody response to Aeromonas salmonicida vaccination was similar in both ploidy. Higher adhesion and melanin scores more likely to occur in triploids and as the anticipated severity of vaccine increased. Triploids heavier in freshwater while diploids were significantly heavier at harvest. Thermal growth coefficient significantly related to increasing severity of adhesions. Higher deformity prevalence in triploids, with no significant effect of vaccine group.